Thermodynamic analysis questions claims of improved cardiac efficiency by dietary fish oil - Loiselle, Denis S. (J Gen Physiol, 2016)
Studies in the literature describe the ability of dietary supplementation by omega-3 fish oil to increase the pumping efficiency of the left ventricle. Here we attempt to reconcile such studies with our own null results. We undertake a quantitative analysis of the improvement that could be expected theoretically, subject to physiological constraints, by posing the following question: By how much could efficiency be expected to increase if inefficiencies could be eliminated? Our approach utilizes thermodynamic analyses to investigate the contributions, both singly and collectively, of the major components of cardiac energetics to total cardiac efficiency. We conclude that it is unlikely that fish oils could achieve the required diminution of inefficiencies without greatly compromising cardiac performance.